Indonesian Student Protest Hashtags and Pragmatic Strategies: Politeness, Impoliteness, and Digital Resistance - Hendar; Heri Heryono; Deden Novan Setiawan Nugraha (PT. Global Research Collaboration, 2026)
The rapid growth of digital activism in Indonesia has positioned social media as a central space for political expression and protest mobilization. However, limited research has examined the micro-pragmatic mechanisms underlying protest discourse, particularly the use of politeness and impoliteness strategies within collectivist sociocultural contexts. This study investigates how politeness and impoliteness are strategically employed in protest hashtags during the Indonesian student protests of August 2025. Specifically, it aims to identify the pragmatic strategies used in protest hashtags, explain their sociocultural motivations, and examine their role in constructing digital solidarity and resistance. Using a qualitative discourse-pragmatic approach, the study analyses 1,000 anonymized public posts collected from X through an integrated framework combining politeness theory, impoliteness theory, relational work, and hashtag discourse analysis. The findings indicate that positive politeness strategies constitute the largest proportion of the dataset and play an important role in fostering collective identity and moral alignment. Negative politeness enables respectful yet firm dissent consistent with Indonesian values of social harmony (rukun), while impoliteness strategies, including direct imperatives and sarcasm, function as forms of morally grounded resistance toward institutional authority. Importantly, politeness and impoliteness operate cooperatively rather than oppositely in constructing a discourse of digital resistance characterized by solidarity, urgency, and moral legitimacy. These findings contribute to digital pragmatics by demonstrating how culturally grounded communication norms are reconfigured in online protest discourse.